109k views
3 votes
I learned this so long ago & i don’t remember how to do it. plz help

I learned this so long ago & i don’t remember how to do it. plz help-example-1
User Sumeshk
by
5.3k points

2 Answers

5 votes

-77.5 is the answer to your question

User Alpar
by
5.4k points
7 votes

#12)

Average rate of change =[f(2) - f(1)] / (x2 - x1)

In this case

Average rate of change =[g(3) - g(-2)] / (x(3) - x(-2))

= (12.5 - 400)/(3 - (-2))

= - 387.5 / 5

= - 77.5

Answer:

Average rate of change = -77.5

User Hivert
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.